Asymmetry : [large type] / a novel - Halliday, Lisa (Wheeler Publishing large print hardcover, 2019)
"Told in three distinct and uniquely compelling sections, Asymmetry explores the imbalances that spark and sustain many of our most dramatic human relations: inequities in age, power, talent, wealth, fame, geography, and justice. The first section, "Folly," tells the story of Alice, a young American editor, and her relationship with the famous and much older writer Ezra Blazer. A tender and exquisite account of an unexpected romance that takes place in New York during the early years of the Iraq War, "Folly" also suggests an aspiring novelist's coming-of-age. By contrast, "Madness" is narrated by Amar, an Iraqi-American man who, on his way to visit his brother in Kurdistan, is detained by immigration officers and spends the last weekend of 2008 in a holding room in Heathrow. These two seemingly disparate stories gain resonance as their perspectives interact and overlap, with yet new implications for their relationship revealed in an unexpected coda. A stunning debut from a rising literary star, Asymmetry is an urgent, important, and truly original work that will captivate any reader while also posing arresting questions about the very nature of fiction itself. A debut novel about love, luck, and the inextricability of life and art, from 2017 Whiting Award winner Lisa Halliday" --